NARRATIVE REVIEW: MONSTERA DELICIOSA SEBAGAI ANTIBAKTERI DALAM SEDIAAN SPRAY HYDROGEL 3 IN 1 - Regina Desyca Sarmitha Dewi; Miftahul Janna; La Ode Muh Alfiqra; Selpirahmawati Saranani (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2021)
Introduction: Monstera deliciosa have the potential to be developed as anti-bacterial drugs due to secondary metabolite compounds such as tannins, steroids, saponins, flavonoids and alkaloids. The purpose of this review is to demonstrate potential of Monstera deliciosa as an antibacterial in spray hydrogel 3 in 1 spray dosage form. Methods: This narrative review conducted the method of literature review or the secondary data compilation from several scientific journal such as wiley, sciencedirect, portal garuda, and google scholar. Result: Monstera deliciosa have several volatile components that have been shown antibacterial activity included 1,6-Cyclodecadiene, 6,10,14-trimethyl-2-Pentadecanone, naphthalene, limonene, 1–methyl–5–methylene–8-(1-methylethyl), and 2-Furanmethanol so it can be used as an antibacterial agent in spray hydrogel 3 in 1 spray dosage form. Conclusion: Monstera deliciosa have the potential to be developed as anti-bacterial in hydrogel 3 in 1 preparation.